2015
DOI: 10.1007/s11999-015-4249-2
|View full text |Cite
|
Sign up to set email alerts
|

A High-grade Sarcoma Arising in a Patient With Recurrent Benign Giant Cell Tumor of the Proximal Tibia While Receiving Treatment With Denosumab

Abstract: Background A giant cell tumor of bone is a primary benign but locally aggressive neoplasm. Malignant transformation in a histologically typical giant cell tumor of bone, without radiotherapy exposure, is an uncommon event, occurring in less than 1% of giant cell tumors of bone. Although surgery is the standard initial treatment, denosumab, a monoclonal antibody drug that inhibits receptor activator of nuclear factor-jB ligand (RANKL), has shown considerable activity regarding disease and control of symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…In August 2015 (1 month after embolization and 2 weeks after beginning denosumab treatment), axial computed tomography showed a continued increase in the size of the osteolytic lesion and sclerotic formation (arrow) in the left body of the ischium. in the three above-mentioned case reports and the present case, respectively (7,8). Our institute previously reported that the latent periods between diagnosis of benign GCTB and diagnosis of secondary malignant GCTB were 16.0, 27.0, 16.3, 22.0, 27.7 and 7.3 years (mean, 19.4 years) in six patients who received neither radiotherapy nor denosumab treatment (13).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In August 2015 (1 month after embolization and 2 weeks after beginning denosumab treatment), axial computed tomography showed a continued increase in the size of the osteolytic lesion and sclerotic formation (arrow) in the left body of the ischium. in the three above-mentioned case reports and the present case, respectively (7,8). Our institute previously reported that the latent periods between diagnosis of benign GCTB and diagnosis of secondary malignant GCTB were 16.0, 27.0, 16.3, 22.0, 27.7 and 7.3 years (mean, 19.4 years) in six patients who received neither radiotherapy nor denosumab treatment (13).…”
Section: Discussionsupporting
confidence: 59%
“…In six cases of secondary malignancy in GCTB after previous radiotherapy, the interval between the start of radiotherapy and diagnosis of the malignancy was 1.7-15.0 years (mean, 8 years) (13). Conversely, in the three above-mentioned case reports and the present case, the interval between the start of denosumab and diagnosis of the malignancy was 0.5-2.5 years (mean, 1.2 years) (7,8). The interval between the start of denosumab and diagnosis of the malignancy is obviously shorter than the interval between the start of radiotherapy and the diagnosis.…”
Section: Discussionmentioning
confidence: 46%
“…The local recurrence rate was similar in patients previously treated with curettage alone. 1 Previous studies found instances of sarcomatous transformation arising in GCTBs treated with denosumab, 23,24 and there have been several suggestions regarding the ideal length of denosumab therapy and monitoring procedures. 22,[25][26][27] Further studies are required to determine the best therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a concern that young patients receive a potentially life-long treatment, considering the risk of long-term side effects and a potential risk of malignant transformation. Sarcomatous transformation of GCTB has been reported during treatment with denosumab, but whether the malignancies were caused by denosumab is unclear [12,13]. Nevertheless, these concerns indicate that surgery should still be the preferred option for resectable tumors.…”
Section: Discussionmentioning
confidence: 99%